Engineering of polymer-based materials for thermal management solutions. (January 2022) - Maqbool, Muhammad; Aftab, Waseem; Bashir, Akbar; Usman, Ali; Guo, Haichang; Bai, Shulin
Abstract: The demand for thermal management tools has triggered the fast development of materials that efficiently manipulate thermal energy. Pristine polymers and their composites have been extensively investigated in this regard owing to their good chemical, mechanical, and thermal properties, lightweight, low cost, and easy processing. Herein, we aim to provide a better understanding of multi-physics thermal transport phenomena, engineering polymeric materials for better overall thermal transport performance, and integrating polymer based thermal management materials (poly-TMMs) with potential applications. We start by presenting the fundamentals of heat transfer in polymeric materials and then discuss the polymer engineering strategies to conduct, radiate, and store thermal energy for thermal management of electronic devices, human body, and other heat-producing devices. We finish by offering the exciting research opportunities available to design new materials for thermal manipulation. We hope that our efforts will facilitate the engineering community to design future polymer based thermal-efficient materials to meet the increasing demand for advanced applications. Graphical abstract: Image 1 Highlights: Fundamentals of heat transfer in different materials are discussed. Strategies for developing various kinds of polymeric thermal management materials (poly-TMMs) are reviewed and discussed in details. Important parameters related to thermal management of all poly-TMMs are described in the form of table in each section. Applications of poly-TMMs in cooling of electronic devices and thermoregulation of the human body are described. The exciting research opportunities available to design new materials for thermal manipulation are also discussed.